Synthesis and characterization of Fe-containing biphasic calcium phosphate ceramics - Kaygili, Omer (Springer, 2019)
Three biphasic calcium phosphate (BCP) ceramics with various Fe contents (e.g., 0.66, 1.32, and 1.98at.%) were prepared using wet chemical synthesis. X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, differential thermal analysis (DTA), thermogravimetric analysis (TG), scanning electron microscopy (SEM), and energy dispersive X-ray (EDX) spectroscopy techniques were used to characterize the as-prepared BCPs. The DTA and TG results show that the as-prepared samples are thermally stable. The addition of Fe affects significantly the lattice parameters, unit cell volume, and morphology. The EDX data confirm the introduction of Fe.
Keywords: Hydroxyapatite; Wet chemical synthesis; Scanning electron microscopy (SEM); X-ray diffraction (XRD)